A Cardio-Obstetric Approach to Management of the Complex Pregnant Cardiac Patient - Verma, Amanda K. (JACC Case Rep, 2020)
A 23-year-old female presented at 28.5 weeks gestation with symptomatic heart failure due to severe mitral stenosis and severe pulmonary arterial hypertension. After multidisciplinary planning, she underwent caesarean delivery with mitral valve replacement 48 h postpartum. Cardio-obstetric teams provide expert coordinated care for complex cardiovascular disease in pregnancy. (Level of Difficulty: Beginner.)